مطبوعة محاضرات في مقياس منهجية البحث العلمي - خلادي ، مراد (Mohamed Boudiaf University of M'Sila, 2025)
الملخص بالعربية : تشمل المطبوعة على أربعة عشر محاضرة، حيث تناولت المطبوعة في البداية أساليب التفكير العلمي، ثم مشكلة واشكالية الدراسة، ثم بعد ذلك الفرضيات في البحوث العلمية، ثم أدوات البحث العلمي، ثم بعد ذلك الخصائص السيكومترية والمعالجات الاحصائية، واخيرا مجتمع وعينة البحث و طرق كتابة التوثيق . Searchlight in English The publication consists of fourteen lectures. The publication first deals with the methods of scientific thinking, then the issue and problem of the study, then hypotheses in scientific research, then scientific research tools, then psychometric properties and statistical treatments, and finally the population and sample of the research and methods of writing documentation
Keywords: منهجية; البحث; العلمي